Factors Affecting Length of Inpatient Forensic Stay: Retrospective Study From Czechia - Páv, Marek; Vňuková, Martina; Sebalo, Ivan (Frontiers in Psychiatry, 2022)
Abstract Objectives: Length of forensic stay (LoS) is a subject of country-specific legal and service system differences. Identification of common factors targetable by treatment is therefore at the forefront of forensic psychiatry research. We bring one of the first reports of forensic patients' characteristics from the Czech Republic. Methods: We conducted a retrospective analysis of data from 260 dismissed inpatients from the Bohnice hospital (Prague) and obtained a set of sociodemographic, clinical variables as well as HoNOS and HoNOS-secure scores. Results: The following variables were identified as significantly associated with longer LoS: higher age, previous psychiatric hospitalization length, olanzapine equivalent, clozapine treatment, psychosocial dysfunction, psychotic or paraphilic disorder diagnosis, committing sex offense. Shorter LoS is predicted by being in a relationship, being employed before the hospitalization, having personal support, and committing index offense under substance influence. While HoNOS score and HoNOS symptoms subscale predicted longer LoS, HoNOS-secure subscale predicted shorter stay. Conclusion: Within the European context, our hospital has relatively low LoS. The results are consistent with findings linking psychotic disorders and paraphilia with longer LoS in forensic treatment. Higher antipsychotic medication doses or clozapine prescriptions are linked to longer LoS. Results show a high level of unmet needs in this population, highlighting the importance of follow-up services availability.